Konstruksi Keluarga Sakinah sebagai Basis Kesejahteraan Psikososial Keluarga - Luvia Wahid (Journal of Health, Medical, and Psychological Studies, 2025)
This study examines the construction of sakinah families as a foundational basis for family psychosocial wellbeing by integrating Islamic values with social and psychological perspectives. The concept of sakinah is understood not merely as the absence of conflict, but as a dynamic process shaped by emotional security, relational justice, spiritual awareness, and adaptive social interaction. Through a qualitative descriptive-analytical approach, this study explores how values of sakinah, mawaddah, and rahmah are internalized and actualized in everyday family life. The findings indicate that psychosocial wellbeing is closely linked to healthy communication patterns, equitable role distribution, religious education within the family, and stable economic management. These elements function collectively as protective factors that strengthen emotional resilience and social harmony within the household. The study also highlights the role of religious institutions and family guidance programs in reinforcing the practical application of sakinah values. Overall, the construction of a sakinah family serves as a holistic model for sustaining psychosocial wellbeing amid contemporary social challenges.